Digestibility and IgE-Binding of Glycosylated Codfish Parvalbumin. (26th June 2013) - de Jongh, Harmen H. J.; Robles, Carlos López; Timmerman, Eefjan; Nordlee, Julie A.; Lee, Poi-Wah; Baumert, Joseph L.; Hamilton, Robert G.; Taylor, Steve L.; Koppelman, Stef J.
Abstract : Food-processing conditions may alter the allergenicity of food proteins by different means. In this study, the effect of the glycosylation as a result of thermal treatment on the digestibility and IgE-binding of codfish parvalbumin is investigated. Native and glycosylated parvalbumins were digested with pepsin at various conditions relevant for the gastrointestinal tract. Intact proteins and peptides were analysed for apparent molecular weight and IgE-binding. Glycosylation did not substantially affect the digestion. Although the peptides resulting from digestion were relatively large (3 and 4 kDa), the IgE-binding was strongly diminished. However, the glycosylated parvalbumin had a strong propensity to form dimers and tetramers, and these multimers bound IgE intensely, suggesting stronger IgE-binding than monomeric parvalbumin. We conclude that glycosylation of codfish parvalbumin does not affect the digestibility of parvalbumin and that the peptides resulting from this digestion show low IgE-binding, regardless of glycosylation. Glycosylation of parvalbumin leads to the formation of higher order structures that are more potent IgE binders than native, monomeric parvalbumin. Therefore, food-processing conditions applied to fish allergen can potentially lead to increased allergenicity, even while the protein's digestibility is not affected by such processing.